Pertimbangan Desain Gigi Tiruan Sebagian Lepasan Resin Akrilik pada Kasus dengan Torus Palatinus - Andini Fitri Zaraswati; Pamungkas Handy Mulyawan; Alicia Putri Dhea; Fauzia Variansiana; Syifa Shafira (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
In the planning of removable partial dentures (RPD), design is a crucial factor that must be tailored to each patient’s clinical condition, while one of the main challenges in RPD design is anatomical variation in the oral cavity such as torus palatinus, which may affect retention, stability, and patient comfort. This report aims to discuss the design considerations of acrylic resin RPD in patients with torus palatinus, particularly in determining optimal design modifications. A 42-year-old female patient presented with complaints of difficulty chewing due to the loss of several teeth in both the maxilla and mandible. Intraoral examination revealed missing teeth 15, 11, and 25, with healthy mucosal and periodontal conditions, and a nodular torus palatinus measuring approximately 2.5 × 2 cm was identified along the midline of the palate. RPD design planning in this case requires an individualized approach, particularly in the selection of the major connector and base adaptation to avoid pressure on the torus area, and design modifications were implemented to improve load distribution and patient comfort. The use of a U-shaped major connector with relief over the torus area effectively avoids direct contact, thereby enhancing comfort, preventing mucosal irritation, and supporting masticatory function.